Effects of Propofol versus Sevoflurane on Postoperative Pain and Neuroendocrine Stress Response in Oocyte Pickup Patients - Yavuz Orak; Fatma İnanç Tolun; Murat Bakacak; Aslı Yaylalı; Hakan Kıran; Hafize Öksüz; Adem Doğaner; Işıl Yağmur; Ahmet Altun (Pain Research and Management)
Background. Pain aggravates the autonomic response to stress and raises neuroendocrine stress hormone levels. We compared the effects of propofol and sevoflurane on postoperative pain and neuroendocrine stress hormones. A prospective, randomized, and controlled trial was conducted with 60 patients. Methods. We randomly allocated patients to groups P (remifentanil/propofol, n = 30) and S (remifentanil/sevoflurane, n = 30). Preoperative blood samples were taken to measure serum adrenocorticotropic hormone (ACTH), corticotropin-releasing hormone (CRH), glucagon, cortisol, aldosterone, and prostaglandin E2 (PGE2) levels. Intraoperatively and postoperatively, clinical parameters were monitored at different time points. The hormone levels were again measured in the follicular fluid and blood postoperatively. Result. Demographic data were similar. The preoperative serum aldosterone levels were significantly higher in group P (p=0.001). Preoperative and postoperative serum ACTH, glucagon, cortisol, and PGE2 levels were significantly different in group P (p=0.009, p=0.004, p=0.029, and p=0.002); serum ACTH, glucagon, and PGE2 levels increased while serum cortisol levels decreased postoperatively. In group S, serum CRH and aldosterone levels, both increased in the postoperative period compared to the preoperative (p=0.001, p=0.006). Postoperatively, glucagon and PGE2 levels were both higher in group P than group S (p=0.019, p=0.015). In postoperative follicular fluid, glucagon and PGE2 levels were higher in group P, while cortisol levels were higher in group S (p=0.001, p=0.007, and p=0.001). Conclusion. The effects of anesthetic agents were different. In group P, in the preoperative and postoperative evaluation, ACTH, glucagon, and PGE2 increased postoperatively, while cortisol decreased. In group S, aldosterone and CRH increased postoperatively. Glucagon and PG E2 were higher in group P than S, postoperatively.